Towards a Landscape-based Regional Design Approach for Adaptive Transformation in Urbanizing Deltas - Steffen Nijhuis; Liang Xiong; Daniele Cannatella (Research in Urbanism Series, 2020)
Deltaic areas are among the most promising regions in the world. Their strategic location and superior quality of their soils are core factors supporting both human development and the rise of these regions as global economic hubs. At the same time, however, deltas are extremely vulnerable to multiple threats from both climate change and the rush to urbanization. These include an increased flood risk combined with the resulting loss of ecological and social-cultural values. The urbanization of deltas can be understood as a set of complex social-ecological systems (and subsystems), each with its own dynamics and speed of change. To ensure a more sustainable future for these areas, spatial strategies are needed to strengthen resilience, i.e. help the systems to cope with their vulnerabilities as well as enhance their capacity to overcome natural and artificial threats. In this article we elaborate a landscape-based regional design approach for the adaptive urban transformation of urbanizing deltas, taking the Pearl River Delta as a case study. Based on an assessment of the dynamics of change regarding the transformational cycles of natural and urban landscape elements, eco-dynamic regional design strategies are explored to reveal greater opportunities for the exploitation of natural and social-cultural factors within the processes of urban development. Furthermore, adaptive transformational perspectives are identified toensure reduced flood risk and inclusive socio-ecological design.